Pertanggungjawaban Pidana Seorang Wanita Pelaku Kekerasan Seksual terhadap Anak di Bawah Umur - Bayu Prasetyo; Sri Setyadji (Harmonization : Jurnal Ilmu Sosial, Ilmu Hukum, dan Ilmu Ekonomi, 2023)
Children are the most beautiful gift from God that we must protect and guide because they are people who believe in God. Children have the right to obtain their rights including the right to education, the right to a place to live, the right to love, must be recognized by parents so that children do not become easily influenced and are still in a condition of parental control. Many children do not get their rights as a child, for example children are abandoned on the streets and experience physical and sexual violence. Violence against children is widespread in homes, schools, and public places. As a result of violence, children experience a form of depression, become quiet individuals, feel afraid when in public places, and tend to speak little. Attempts must be made to stop acts of violence against children so that no more children arise as victims. We must help children as victims, fight for their rights and protect their confidentiality. Therefore, children who are victims of sexual violence need psychological assistance so that these children can continue to live happily in the future. Acts of sexual harassment, whether mild (for example verbally) or serious (such as rape) are acts of attack and harm to individuals, in the form of privacy rights and related to sexuality. Likewise, it attacks the public interest in the form of guaranteed human rights which must be respected collectively.